2014
DOI: 10.1523/jneurosci.5359-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Neural Stem Cell Grafts in the Lesioned Spinal Cord Is Enhanced by a Combination of Treadmill Locomotor Training via Insulin-Like Growth Factor-1 Signaling

Abstract: Combining cell transplantation with activity-based rehabilitation is a promising therapeutic approach for spinal cord repair. The present study was designed to investigate potential interactions between the transplantation (TP) of neural stem cells (NSCs) obtained at embryonic day 14 and treadmill training (TMT) in promoting locomotor recovery and structural repair in rat contusive injury model. Combination of TMT with NSC TP at 1 week after injury synergistically improved locomotor function. We report here th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 61 publications
1
76
2
Order By: Relevance
“…In this study, both therapeutic approaches led to a mitigation of motor deficits, in terms of impairment of motor coordination and lack of accuracy in paw placing. However, despite the synergic effects that were described in some studies using combined treatment for traumatic pathologies in the nervous system (Hwang et al, ; Nicola et al, ), the synergistic effect on motor function in our combined group was negligible.…”
Section: Discussioncontrasting
confidence: 63%
“…In this study, both therapeutic approaches led to a mitigation of motor deficits, in terms of impairment of motor coordination and lack of accuracy in paw placing. However, despite the synergic effects that were described in some studies using combined treatment for traumatic pathologies in the nervous system (Hwang et al, ; Nicola et al, ), the synergistic effect on motor function in our combined group was negligible.…”
Section: Discussioncontrasting
confidence: 63%
“…Moreover, it must be kept in mind that cell survival or neural network formation alone may not be adequate to achieve functional recovery, as shown in previous research (Sharp et al, ). To obtain functional recovery, combined therapy with rehabilitation and/or medications should also be considered to facilitate neuronal connections and to improve the treatment effect of scaffolds (Dobrossy et al, ; Hwang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…33 Several studies have reported that IGF-1 attenuates the damage associated with SCI, and reduces the stress-induced tissue swelling and electrophysiological imbalance of the spinal cord. [34][35][36] An important effect of IGF-1 is its involvement with the control of axonal growth, because IGF-1 specifically enhances the extent and rate of murine corticospinal motor neuron axonal outgrowth in culture. 37 Interestingly, the incretins GIP and GLP are positive modulators of the effects of insulin, expression of IGF-1 receptor, neuronal plasticity, neurogenesis, and neuroprotection.…”
Section: Discussionmentioning
confidence: 99%